BIOMONITORING DAMPAK EKOLOGIS MERKURI DI DAERAH ALIRAN SUNGAI TORAUT KABUPATEN BOLAANG MONGONDOW - Rantung, John L.; Wantasen, Sofia (Universitas Sam Ratulangi, 2016)
ABSTRACT Traditional gold mining in Toraut Watershed Bolaang Mongondow District was used Merkuri Amalgamation that produced tailing. Tailing are discharged to river and environment sorounding that can enter Toraut River and flows to the down stream Mongondow river (beach Inobonto). This study aims: 1) To determine Hg concentrations in River Toraut up stream, middle stream and down stream; 2) To determine Hg concentrations in sediment of the River Toraut up stream, middle stream and down stream; 3) To determine Hg concentrations in aquatic plantsof the River Toraut up stream, middle stream and down stream.Â Location research in River Toraut up stream, middle stream and down stream. Data collected by observation and laboratory analysis Merkuri concentration in River Toraut, sediment, and aquatic plant. Method data analysis are descriptif, Graphic Method and to compare with standart Goverment PP. No.82/2001 Class II. The analysis showed that the concentration of Merkuri in River Toraut up stream, in the middle stream and down stream is<0.00005 mg/l. The concentration of Merkuri in sediments River Toraut up stream, the middle stream and down stream ranged < 0.05-1.45 mg/kg dry. The concentration of Merkuri in tissue plant aquatic location up stream of the River Toraut, the middle stream and down stream range < 0.001-0.013 mg /kg wet.Keywords : biomonitoring, ecological impacts merkuri, Toraut Watershed